Elementary and Pre-Service Teachers' Strategies for Working with Students with Hyperactivity - John L. Nietfeld; Angela A. Hunt (Arizona State University, 2015)
This study investigated the types of interventions that elementary school teachers and pre-service teachers choose to employ when working with students displaying hyperactive behavior. The extent to which beliefs systems, namely entity/incremental theories, showed relationships with the selection of particular types of interventions was also examined. Participants were presented with fictional scenarios of students that varied according to the level of ADHD-like behaviors exhibited and were then asked to provide appropriate interventions. Overwhelmingly, the teachers in this study chose behavioral interventions (e.g., reinforce appropriate behavior) over more clinical or medical options (e.g., refer for ADHD diagnosis). However, the teachers did not differentiate their interventions in a manner consistent with the qualifications of ADHD as described in the DSM-IV. In addition, entity/incremental beliefs revealed an inconsistent relationship with the choice of intervention.